Compressed ultrafast photography by multi-encoding imaging. (3rd October 2018) - Yang, Chengshuai; Qi, Dalong; Liang, Jinyang; Wang, Xing; Cao, Fengyan; He, Yilin; Ouyang, Xiaoping; Zhu, Baoqiang; Wen, Wenlong; Jia, Tianqing; Tian, Jinshou; Gao, Liang; et al.
Abstract: Imaging ultrafast dynamic scenes has been long pursued by scientists. As a two-dimensional dynamic imaging technique, compressed ultrafast photography (CUP) provides the fastest receive-only camera to capture transient events. This technique is based on three-dimensional image reconstruction by combining streak imaging with compressed sensing (CS). However, the image quality and the frame rate of CUP are limited by the CS-based image reconstruction algorithms and the inherent temporal and spatial resolutions of the streak camera. Here, we report a new method to improve the temporal and spatial resolutions of CUP. Our numerical simulation and experimental verification show that by using a multi-encoding imaging method, both the image quality and the frame rate of CUP can be significantly improved beyond the intrinsic technical parameters. Importantly, the temporal resolution by our scheme can break the limitation of the streak camera. Therefore, this new technology has potential benefits in many applications that require the ultrafast dynamic scene image with high temporal and spatial resolutions.